Current Economic Recession : Concept, Causes and Effects - Agarwal, M. L; Bansal, Anshu (Journal of Commerce and Trade, 2009)
The term Business cycle or Economic cycle refers to the fluctuations of economic activity (business fluctuations) around its long-term growth trend. The cycle involves shifts over time between periods of relatively rapid growth of output (recovery and prosperity), and periods of relative stagnation or decline (contraction or recession). These fluctuations are often measured using the GDP. Traditional business cycles undergo four stages: expansion, prosperity, contraction, and recession. The phases of the business cycle are characterized by changing employment, industrial productivity, and interest rates. Some economists believe that stock price trends precede business cycle stages. Despite being termed cycles, the Recession of 2008 is the next Globalization, privatization and Industrialization has made the counties so interdependent that a change in any economic barometer, in any country especially which is economically strong, is felt in other countries too. In the light of above states facts this article deals to understand: what is an economic recession? How it has affected the Indian industries? What are the remedies to get rid off this problem/How to respond to a recession?